Impact of tricuspid regurgitation on right ventricular myocardial work in patients with pulmonary hypertension: a pilot study - Mauro Acquaro; Claudio Di Lorenzo; Laura Scelsi; Annalisa Turco; Alessandra Greco; Carmine Spirito; Beatrice Pasotti; Sandra Schirinzi; Catherine Klersy; Guido Tavazzi; Stefano Ghio (Exploration of Cardiology)
Aim: Significant tricuspid regurgitation (TR) may be a confounding factor when assessing right ventricular (RV) function with imaging techniques. Global myocardial work (GMW) has been proposed as a non-invasive surrogate of RV pressure–volume loops, and it might provide a more accurate evaluation of RV performance than standard echocardiographic parameters, accounting for both afterload and myocardial work efficiency. The aim of this study was to assess the relationship between RV GMW and hemodynamic indices of prognostic significance in pulmonary hypertension (PH) and to compare RV GMW in PH patients with or without TR. Methods: This was a proof-of-concept study. Thirty consecutive patients with PH undergoing diagnostic right heart catheterization (RHC) in sinus rhythm were enrolled. Echocardiography was performed in all patients within two hours of RHC. Results: Global work efficiency (GWE) was directly correlated (r = 0.562, p = 0.006), whereas global wasted work (GWW) was inversely correlated with stroke volume index (r = –0.447, p = 0.037). Poorer correlation was observed with tricuspid annular plane systolic excursion (TAPSE), and no correlation was observed with TAPSE/sPAP (ratio of TAPSE to systolic pulmonary artery pressure). Patients with moderate/severe TR had lower GWE [83% (77–89%) vs. 96% (94–96%), p < 0.001] and higher GWW [137% (90–179%) vs. 25% (18–89%), p = 0.002]. Similar results were obtained when the analysis was applied to subgroups of patients stratified according to either preserved or poor TAPSE/sPAP. Conclusions: RV myocardial work is more strongly associated with hemodynamic indicators of prognosis in PH than standard echocardiographic parameters. Patients with moderate/severe TR have significantly lower values of work efficiency and higher values of wasted work as compared to those without significant TR.